Biotic interactions affecting the reproductive success of Antarctic beech (Nothofagus moorei) - Amy Leigh Smart (2021)
Nothofagus moorei (Antarctic Beech) is the dominant canopy tree of many remaining fragments of cool temperate rainforests of northern NSW and south-eastern Queensland. Despite being an iconic species there is a paucity of information (especially quantitative data) concerning life history stages and processes that together determine reproductive success. In this thesis I made significant advances towards closing this knowledge gap. First, pre-dispersal fruit/seed predation by birds and insects was quantified, revealing a decreasing amount of predation later in the masting season - in accordance with the "predator starvation/satiation" hypothesis. Second, the proportion of juveniles that were derived from seed or vegetative regeneration was quantified, both for N. moorei and co-occurring tree species. While there was a higher abundance of seedlings, juveniles of vegetative origin exhibited superior relative height. Third, I quantified the influence of soil-litter disturbing vertebrates on juvenile tree success. While, overall, survivorship and growth were higher in the presence of soil disturbing vertebrates, Antarctic Beech juveniles exhibited enhanced survival when protected from physical disturbance. These findings provide a greater understanding of the mechanisms underpinning stand dynamics and canopy renewal of Antarctic Beech and co-occurring tree species in an ecologically unique vegetation type under increasing threat from climate change.